Mityczno-symboliczny kontekst nostalgii w „Wygnaniu” Andrieja Zwiagincewa w świetle antropologicznej niepewności podmiotu - Przybysz, Anna Katarzyna (Studia Rossica Posnaniensia, 2019)
The aim of this article is to reveal the mythical, symbolic and religious context in the film The Banishment. We also try to show how the nostalgia felt by the heroine can be associated with the state of anthropological uncertainty.